Optical Fiber
By incorporating a chlorine-doped core and optimizing the refractive index and residual stress in the optical fiber, the challenges of high transmission losses in Ge-doped cores are addressed, achieving reduced Rayleigh scattering and improved transmission efficiency.
Patent Information
- Application Number
- JP2022501983
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-21
- Filing Date
- 2021-02-18
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-02-18
AI Technical Summary
Existing optical fibers with Ge-doped cores experience high Rayleigh scattering losses due to concentration fluctuations, which hinder the reduction of transmission losses.
The optical fiber incorporates a silica-based glass core with a mass fraction of 1% or more chlorine (Cl) and a cladding with a refractive index lower than the core's maximum refractive index, ensuring consistent residual stress across the glass portion's cross-section.
This configuration reduces transmission losses by minimizing Rayleigh scattering, with further reductions achieved by adding fluorine (F) to the core and optimizing the refractive index profile and residual stress distribution.
Smart Images

Figure 0007666497000002 
Figure 0007666497000003 
Figure 0007666497000004
Abstract
Description
[Technical field]
[0001] TECHNICAL FIELD This disclosure relates to optical fibers. This application claims priority from Japanese Patent Application No. 2020-028324, filed on February 21, 2020, the contents of which are relied upon and incorporated herein by reference in their entirety. [Background technology]
[0002] For example, an optical fiber made of silica-based glass with germanium (Ge) doped in the core is known. In such an optical fiber with a Ge-doped core, Rayleigh scattering loss caused by the fluctuation in the Ge concentration (variation from the average value) is large, and the doping of Ge in the core is becoming an obstacle to reducing transmission loss. As a countermeasure, optical fibers are being manufactured in which the core is not doped with Ge, but the cladding is doped with fluorine (F), for example, in order to reduce loss. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. WO2016 / 007806A1 [Non-patent literature]
[0004] [Non-Patent Document 1] Libert et al, IWCS_Proceedings (1998) 375 [Non-Patent Document 2] MP Varnham et al, Electron Lett 20, 1034 (1984) Summary of the Invention
[0005] The optical fiber of the present disclosure includes a glass portion made of silica-based glass. The glass portion includes a core including a central axis and a cladding surrounding the core. The core is doped with chlorine (Cl) at a mass fraction of 1% or more. The cladding has a refractive index lower than the maximum refractive index of the core. Furthermore, residual stress is substantially consistent across the entire cross section of the glass portion perpendicular to the central axis. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 is a diagram showing a cross-sectional structure of an optical fiber according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a table showing the specifications of each of Samples 1 to 5 of the optical fiber according to an embodiment of the present disclosure. [Diagram 3] FIG. 3 is a graph showing the relationship between the mass fraction (%) of chlorine (Cl) and the transmission loss (dB / km) for each of Samples 1 to 5. [Figure 4] FIG. 4 is a table showing the specifications of each of Samples 6 to 9 of the optical fiber according to an embodiment of the present disclosure. [Diagram 5] FIG. 5 is a graph showing the relationship between the mass fraction (%) of fluorine (F) and the transmission loss (dB / km) for each of Samples 6 to 9. [Figure 6] FIG. 6 is a table showing the specifications of Samples 10 to 13 of the optical fiber according to an embodiment of the present disclosure, together with the specifications of Sample 5 (reference). [Figure 7] FIG. 7 is a graph showing the relationship between the difference between the maximum and minimum residual stress (MPa) and the transmission loss (dB / km) for each of Sample 5 (reference) and Samples 10 to 13. [Figure 8] FIG. 8 is a table showing the specifications of Samples 14 to 16 of the optical fiber according to an embodiment of the present disclosure, together with the specifications of Sample 5 (reference). [Figure 9]FIG. 9 is a graph showing the relationship between the effective cross-sectional area Aeff (μm 2 ) and the transmission loss (dB / km) for each of Sample 5 (reference) and Samples 14 to 16. [Figure 10] FIG. 10 is a table showing the specifications of each of Samples 17 to 23 of the optical fiber according to an embodiment of the present disclosure, together with the specifications of Sample 5 (reference). [Figure 11] FIG. 11 is a graph showing the relationship between the α value and the transmission loss (dB / km) for each of Sample 5 (reference) and Samples 17 to 23. [Figure 12] FIG. 12 is a table showing the specifications of Samples 24 to 26 of the optical fiber according to an embodiment of the present disclosure, together with the specifications of Sample 5 (reference). [Figure 13] FIG. 13 is a graph showing the relationship between the difference in residual stress (MPa) between specific portions and the transmission loss (dB / km) for each of Samples 24 to 26 as well as Sample 5 (reference). [Figure 14] FIG. 14 is a table showing the specifications of each of Samples 27 to 31 of the optical fiber according to an embodiment of the present disclosure, together with the specifications of Sample 5 as a reference example. [Figure 15] FIG. 15 is a table showing the specifications of each of Samples 32 to 38 of the optical fiber according to one embodiment of the present disclosure. [Figure 16] FIG. 16 is a table showing the specifications of Samples 39 to 41 of the optical fiber according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] [Problem that this disclosure aims to solve] The inventors have studied the conventional manufacturing method of the optical fiber preform and found the following problem. That is, Patent Document 1 describes that the transmission loss can be reduced by setting the viscosity of the core region (region to become the core of the optical fiber after drawing) of the preform to be equal to or lower than the viscosity of the cladding region (region to become the cladding of the optical fiber after drawing) and by matching the coefficient of thermal expansion (CTE) between the core region and the cladding region. However, as described in Patent Document 1, simply bringing the viscosity and the coefficient of thermal expansion between the core region and the cladding region in the preform closer to each other is insufficient to reduce the transmission loss. This is because the stress remaining in the glass region is affected not only by the properties of the preform such as the viscosity and the coefficient of thermal expansion, but also by the tension, drawing speed, and the method of annealing during drawing.
[0008] The present disclosure has been made to solve the above-mentioned problems, and has an object to provide an optical fiber having a structure capable of reducing an increase in transmission loss.
[0009] [Effects of this disclosure] The optical fiber of the present disclosure makes it possible to reduce transmission loss.
[0010] [Description of the embodiment of the present invention] First, the contents of the embodiments of the present disclosure will be individually listed and described.
[0011] (1) In one embodiment of the optical fiber according to the present disclosure, the optical fiber includes a glass portion made of silica-based glass. The glass portion includes a core including a central axis and a cladding surrounding the core. The core is doped with chlorine (Cl) at a mass fraction of 1% or more. The cladding has a refractive index lower than the maximum refractive index of the core. Furthermore, the residual stress is substantially consistent throughout the cross section of the glass portion perpendicular to the central axis. Specifically, the "state in which the residual stress is substantially consistent" means a state in which the difference between the maximum and minimum values of the residual stress is 230 MPa or less, or 200 MPa or less, and more preferably, in one embodiment of the present disclosure, the difference between the maximum and minimum values of the residual stress is 100 MPa or less. In the present application, the "residual stress" refers to the axial stress σz described in Non-Patent Document 2. This is a component of the stress parallel to the AX direction acting on a cross section perpendicular to the AX direction in FIG. 1, and when it has a positive value, it is a tensile stress, and when it has a negative value, it is a compressive stress.
[0012] As mentioned above, in an optical fiber in which the core is doped with 1% or more Cl by mass fraction, if the difference (absolute value) between the maximum and minimum residual stress in the glass part is 230 MPa or less, or 200 MPa or less, an optical fiber with lower loss can be obtained compared to conventional technology. If the difference (absolute value) between the maximum and minimum residual stress is 100 MPa or less, the effect of reducing loss becomes more pronounced. This is thought to be because a high Cl concentration reduces the glass viscosity, making it easier to reduce Rayleigh scattering loss due to the gradual cooling effect when cooling the optical fiber (optical fiber after drawing) after it has been heated once in the drawing furnace.
[0013] (2) In one embodiment of the present disclosure, the core may further contain fluorine (F). That is, by adding an appropriate amount of F, the glass viscosity is further reduced, and therefore the effect of reducing Rayleigh scattering loss can be obtained.
[0014] (3) The mass fraction of chlorine added to the core may be 1.5% or more. In this case, a further reduction in Rayleigh scattering loss can be obtained. However, in one embodiment of the present disclosure, the mass fraction of chlorine added to the core is preferably 5% or less, and more preferably 3% or less. If the mass fraction of chlorine exceeds 5% (or even 3% or more in some cases), bubbles may be generated during the addition of chlorine, which may make it difficult to manufacture the optical fiber preform.
[0015] (4) In one aspect of this embodiment, the optical fiber has a diameter of 70 μm. 2 More than 150μm 2 The effective cross section A eff In this case, a sufficient reduction in transmission loss can be expected.
[0016] (5) In one embodiment of the present disclosure, the refractive index profile in the core follows an α-power profile, and the α value that defines the shape is preferably 150 or less. This is because an α value exceeding 150 causes a significant increase in transmission loss. However, in one embodiment of the present disclosure, the α value is preferably 3 or more and 99 or less. The effect of reducing transmission loss is significant when the α value is in the range of 60 or more and 80 or less, but an α value of 3 or more and 99 or less is practical.
[0017] (6) In one embodiment of the present disclosure, the average value of the residual stress in a region of the cross section of the glass part that is 50 μm or more and 62.5 μm or less in the radial direction from the center of the cross section is preferably lower than the average value of the residual stress in a region that is 45 μm or more and 55 μm or less in the radial direction from the center of the cross section. By satisfying the above relationship between such different regions, a sufficient effect of reducing Rayleigh scattering loss can be obtained.
[0018] (7) In one embodiment of the present disclosure, the optical fiber preferably has a microbend loss of 1 dB / km or less at a wavelength of 1,550 nm. The microbend loss can be easily controlled by adjusting the Young's modulus of the coating provided on the outer peripheral surface of the glass portion.
[0019] (8) In one embodiment of the present disclosure, the optical fiber preferably experiences an increase in transmission loss of 0.005 dB / km or less at a wavelength of 1550 nm after exposure for 720 hours to a hydrogen atmosphere at a partial pressure of 1.5 kPa and a temperature of 25° C. By controlling the fictive temperature low (for example, below 2000° C.), the increase in transmission loss after treatment in a hydrogen atmosphere is reduced (there are fewer crystal defects in the glass structure).
[0020] As described above, each aspect listed in the [Description of the embodiments of the present disclosure] section is applicable to each of the remaining aspects or to all combinations of these remaining aspects.
[0021] [Details of the embodiment of the present disclosure] Hereinafter, specific structures of optical fibers according to embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Note that the present invention is not limited to these examples, but is indicated by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims. In addition, in the description of the drawings, the same elements are given the same reference numerals, and duplicated descriptions are omitted.
[0022] Fig. 1 is a cross-sectional view showing an example of the structure of an optical fiber according to the present disclosure. In Fig. 1, the optical fiber 100 includes a glass fiber (glass portion) 100a made of silica-based glass, a primary coating 210 provided on the outer peripheral surface of the glass fiber 100a, and a secondary coating 220 provided on the outer peripheral surface of the primary coating 210. The glass fiber 100a includes a core 10 including a central axis (optical axis) AX, and a cladding 20 provided on the outer peripheral surface of the core. The core 10 is doped with chlorine (Cl) at a mass fraction of 1% or more. In addition, the cladding 20 may be doped with an appropriate refractive index reducer such as F, and the refractive index of the cladding 20 is set to be lower than the maximum refractive index of the core 10.
[0023] The primary coating 210 has a thickness (width of the primary coating 210 defined along the radial direction perpendicular to the central axis AX) of 18 μm or more and 33 μm or less. The primary coating 210 has a Young's modulus of 0.05 MPa or more and 0.6 MPa or less. Meanwhile, the secondary coating 220 has a thickness of 20 μm or more and 30 μm or less. The secondary coating 220 has a Young's modulus of 1200 MPa or more and 1500 MPa or less. The ratio of the thickness of the primary coating 210 to the thickness of the secondary coating 220 ("primary thickness" / "secondary thickness") is 0.3 or more and 1.8 or less, preferably 0.9 or more and 1.8 or less. In this case, the microbend loss (dB / km) of the optical fiber 100 with the primary coating 210 and the secondary coating 220 provided can be controlled within an appropriate range.
[0024] Below, the evaluation results of Samples 1 to 41 of the optical fiber 100 of the present disclosure will be described with reference to Figures 2 to 16. As a premise, the specifications shown in Figures 2, 4, 6, 8, 10, 12, and 14 to 16 will be described. Note that F is doped in the cladding of the optical fiber of each sample. (1) "Core Δ(%)": Item (1) is the maximum relative refractive index difference (%) of the core in each sample, and is based on the refractive index n0 of pure silica glass. For example, the relative refractive index difference Δ of a portion having a refractive index n is given by the formula (n / n0)-1. (2) "Core Alpha Value": Item (2) corresponds to the exponent of the definition formula of the "α-power profile" described in the above Patent Document 1, and the profile shape of the core is expressed by this α value. In other words, the refractive index profile of the core in each sample (change in the relative refractive index difference along the radial direction perpendicular to the central axis AX) is expressed by the following definition formula of the "α-power profile":
number
[0025] moreover, (11) 22m cable cutoff wavelength λ cc (μm): Item (11) is the cable cutoff wavelength (μm) defined in ITU-T G650.1. (12) "MFD / λ cc " Item (12) is "22m cable cutoff wavelength λ cc " is the ratio of "MFD" to " (13) "Bending loss @ 1550 nm (dB / roll) (bending diameter 30 mm)": Item (13) is the increase in loss (dB / turn) per turn (turn) measured when light with a wavelength of 1550 nm was input to each sample wound around a mandrel with a diameter of 30 mm. (14) "Bending loss @ 1550 nm (dB / roll) (bending diameter 60 mm)": Item (14) is the increase in loss (dB / turn) per turn measured when light with a wavelength of 1550 nm was input to each sample wound around a mandrel with a diameter of 60 mm. (15) "Transmission loss @ 1550 nm (dB / km)": Item (15) is the transmission loss (dB / km) of each sample at a wavelength of 1550 nm. (16) "Difference between maximum and minimum residual stress (MPa)": Item (16) is a numerical value (MPa) indicating the variation state of residual stress in the entire cross section of the glass portion of each sample (corresponding to the glass fiber 100a shown in FIG. 1). (17) Microbend loss (dB / km): Item (17) is the microbend loss (dB / km) of each sample. The microbend loss was evaluated with reference to Non-Patent Document 1. Specifically, the microbend loss is calculated from the increase in loss when light with a wavelength of 1550 nm is input to each of 500 m of samples wound with a tension of 80 gf around a drum with a diameter of 405 mm and a mesh-like body surface formed by knitting metal wires with a cross-sectional diameter of 50 μm at intervals of 100 μm. (18) "Primary thickness (μm)": Item (18) is the thickness (μm) of the primary coating (corresponding to primary coating 210 shown in FIG. 1) for each sample, i.e., the cross-sectional width of the primary coating along the radial direction. (19) "Secondary thickness (μm)": Item (19) is the thickness (μm) of the secondary coating (corresponding to secondary coating 220 shown in FIG. 1) for each sample, i.e., the cross-sectional width of the secondary coating along the radial direction.
[0026] moreover, (20) "Primary Young's modulus (MPa)": Item (20) is the Young's modulus (MPa) of the primary coating for each sample. (21) "Secondary Young's modulus (MPa)": Item (21) is the Young's modulus (MPa) of the secondary coating for each sample. (22) "Coating thickness ratio": Item (22) is the ratio of the thickness of the primary coating to the thickness of the secondary coating for each sample ("Primary Thickness (μm)" / "Secondary Thickness (μm)"). (23) "Increase in hydrogen loss (dB / km)": Item (23) is the increase in transmission loss (dB / km) at a wavelength of 1550 nm measured for each sample of optical fiber exposed to a hydrogen atmosphere at a partial pressure of 1.5 kPa and a temperature of 25° C. for 720 hours. (24) "Average value of 55-62.5 residual stress (average value of 55-62.5)": Item (24) is the average residual stress (MPa) in the annular region between an inner portion with a radius of 55 μm and an outer portion with a radius of 62.5 μm in the cross section of each sample (a cross section perpendicular to the axis corresponding to the central axis AX shown in Figure 1). (25) "Average value of 45-55 residual stress (45-55 average value)": Item (25) is the average residual stress (MPa) in the annular region between an inner portion with a radius of 45 μm and an outer portion with a radius of 55 μm in the cross section of each sample. (26) "Core average fictive temperature (℃)": Item (26) is the average fictive temperature (°C) of the core for each sample.
[0027] Next, Fig. 2 is a table showing the specifications of each of Samples 1 to 5 prepared as optical fibers according to an embodiment of the present disclosure. Also, Fig. 3 is a graph showing the relationship between the mass fraction (%) of chlorine (Cl) and the transmission loss (dB / km) for each of Samples 1 to 5.
[0028] As can be seen from the measurement results of Samples 1 to 5 shown in Figure 3, the higher the chlorine concentration (mass fraction of chlorine), the lower the transmission loss. This is thought to be because the higher the chlorine concentration, the lower the glass viscosity. In other words, it is thought that the Rayleigh scattering loss is more likely to be reduced by the gradual cooling effect of the drawn optical fiber from immediately after heating in the drawing furnace until it is cooled. Note that when Cl with a mass fraction higher than 3% is added to the core, the generation of bubbles tends to make it difficult to manufacture the optical fiber preform. Therefore, it is appropriate that the mass fraction of Cl added to the core be 5% or less.
[0029] Fig. 4 is a table showing the specifications of each of Samples 6 to 9 of the optical fiber according to an embodiment of the present disclosure. Fig. 5 is a graph showing the relationship between the mass fraction (%) of fluorine (F) and the transmission loss (dB / km) for each of Samples 6 to 9. All of Samples 6 to 9 are optical fibers in which F is co-doped into the core together with Cl at approximately the same concentration.
[0030] As can be seen from the measurement results of Samples 6 to 9 shown in Figure 5, when the mass fraction of F is 0.5% or less, the transmission loss is almost the same, but when the mass fraction of F is 0.5% or more, the transmission loss increases. When the mass fraction of F is 0.5% or less (Samples 6 to 8), the transmission loss is almost the same between the samples. This is thought to be because the reduction in Rayleigh scattering loss due to the decrease in glass viscosity by adding F and the increase in Rayleigh scattering loss due to the concentration fluctuation of F (deviation from the design concentration distribution) are about the same. On the other hand, when the mass fraction of F is 0.5% or more (Sample 9), the effect of reducing Rayleigh scattering loss due to the decrease in glass viscosity begins to saturate, so it is presumed that the increase in Rayleigh scattering loss due to the concentration fluctuation of F will exceed the reduction in Rayleigh scattering loss due to the decrease in glass viscosity. In addition, when comparing Samples 5 to 8, there are cases where the transmission loss is reduced when F is added to the core compared to when no additive is added. The mass fraction of F needs to be 0.1% or more.
[0031] Fig. 6 is a table showing the specifications of Samples 10 to 13 of the optical fiber according to an embodiment of the present disclosure together with the specifications of Sample 5 (reference). Also, Fig. 7 is a graph showing the relationship between the difference between the maximum and minimum residual stress (MPa) and the transmission loss (dB / km) for Samples 10 to 13 as well as Sample 5 (reference).
[0032] As can be seen from the measurement results of Sample 5 and Samples 10 to 13 shown in Figure 7, the smaller the difference between the maximum residual stress and the minimum residual stress among the stresses remaining in the entire cross section of each sample, the lower the transmission loss. This is thought to be because the Rayleigh scattering loss changes due to the refractive index difference caused by the strain inside each sample (optical fiber), especially in the glass part.
[0033] 8 is a table showing the specifications of Samples 14 to 16 of the optical fiber according to an embodiment of the present disclosure together with the specifications of Sample 5 (reference). Also, FIG. 9 shows the effective area A eff ( μm 2 ) and transmission loss (dB / km).
[0034] As can be seen from the measurement results of sample 5 and samples 14 to 16 shown in Figure 9, the effective cross section A eff The larger the effective cross-sectional area A, the smaller the transmission loss. eff This is thought to be because when the F concentration in the cladding of each sample becomes lower due to the expansion of the F concentration, the loss caused by Rayleigh scattering due to F concentration fluctuations in the cladding mode light is reduced.
[0035] Fig. 10 is a table showing the specifications of Samples 17 to 23 of the optical fiber according to an embodiment of the present disclosure together with the specifications of Sample 5 (reference). Also, Fig. 11 is a graph showing the relationship between the α value and the transmission loss (dB / km) for Samples 17 to 23 together with Sample 5 (reference).
[0036] As can be seen from the measurement results of Sample 5 and Samples 17 to 23 shown in FIG. 11, the transmission loss is reduced most when the α value is in the range of 60 to 80. When the α value is smaller than this range or when the α value is larger than this range, the transmission loss tends to increase. The increase in the transmission loss when the α value is smaller is thought to be due to an increase in the glass viscosity at the core periphery, which is caused by a decrease in the Cl concentration at the core periphery. In other words, it is thought that the increase in the glass viscosity at the core periphery increases the Rayleigh scattering loss. On the other hand, the increase in the transmission loss when the α value is larger is not clearly understood, but it can be assumed that the increase in the Cl concentration at the interface between the core and the cladding causes the generation of microbubbles near the interface. In other words, it is assumed that the increase in the transmission loss is due to the phenomenon of an increase in the Rayleigh scattering loss caused by interface mismatch. In addition, when drawing each sample, each sample drawn from the drawing furnace was slowly cooled using a heat-retaining furnace. The temperature of the heat-retaining furnace was different for each sample.
[0037] Fig. 12 is a table showing the specifications of Samples 24 to 26 of the optical fiber according to an embodiment of the present disclosure together with the specifications of Sample 5 (reference). Fig. 13 is a graph showing the relationship between the difference in residual stress (MPa) between specific portions and the transmission loss (dB / km) for Samples 24 to 26 together with Sample 5 (reference). Note that the "difference in residual stress between specific portions" is the difference value obtained by subtracting the average value of residual stress (55-62.5 average value) in a region that is 55 μm or more and 62.5 μm or less from the center of the cross section along the radial direction from the average value of residual stress (45-55 average value) in a region that is 45 μm or more and 55 μm or less from the center of the cross section along the radial direction.
[0038] As can be seen from the measurement results of Sample 5 and Samples 24 to 26 shown in Figure 13, the larger this difference value is, the lower the transmission loss is. Specifically, the difference value defined as "(45-55 average value) - (55-62.5 average value)" is preferably 20 MPa or more. When compressive stress is applied to the outermost periphery where the "glass part outer diameter" is 110 μm or more and 130 μm or less (radius of 55 μm or more and 62.5 μm or less), tensile stress remains in the cladding, and as a result, compressive stress remains in the core where the optical power is concentrated. It can be assumed that this situation reduces Rayleigh scattering loss.
[0039] Next, the increase in transmission loss (increase in hydrogen loss) at a wavelength of 1550 nm was evaluated for each sample after it was exposed for 720 hours to a hydrogen atmosphere at a partial pressure of 1.5 kPa and a temperature of 25° C. Fig. 14 is a table showing the specifications of Samples 27 to 31 of the optical fiber according to an embodiment of the present disclosure, together with the specifications of Sample 5 (reference).
[0040] In the case of Sample 5 and Samples 27 to 31 shown in FIG. 14, the smaller the fictive temperature, the smaller the increase in hydrogen loss (the increase in transmission loss in hydrogen characteristic evaluation). This is thought to be because the lower the fictive temperature, the fewer defects there are in the glass structure. Also, comparing Sample 5, Sample 30, and Sample 31, the higher the Cl concentration in the core, the smaller the increase in hydrogen loss. This is thought to be because the lower the Cl concentration, the more defects there are in the glass structure. Therefore, in order to keep the increase in hydrogen loss to 0.008 dB / km or less, it is thought that the fictive temperature should be 2000°C or less and the mass fraction of CL should be 1% or more.
[0041] Fig. 15 is a table showing the specifications of each of Samples 32 to 38 of the optical fiber according to an embodiment of the present disclosure. In Fig. 15, the microbend loss (measured with both the primary coating and the secondary coating provided) of Samples 32 to 38 is additionally shown.
[0042] Comparing Samples 32 to 38 in the diagram of Figure 15, the primary coating thickness "primary thickness" and the secondary coating thickness "secondary thickness" are similar, and the relationship between their Young's modulus and microbend loss can be obtained. When the Young's modulus of the primary coating "primary Young's modulus" is greater than 0.5 MPa and the Young's modulus of the secondary coating "secondary Young's modulus" is greater than 500 MPa, the microbend loss can be suppressed to 1 dB / km or less.
[0043] Fig. 16 is a table showing the specifications of Samples 39 to 41 of the optical fiber according to the embodiment of the present disclosure. Comparing Samples 39 to 41 shown in Fig. 16, in which the Young's modulus of the primary coating and the Young's modulus of the secondary coating are fixed and the thicknesses of these coatings are changed, when the outer diameter of the primary coating is smaller than 160 µm (Sample 39: 161 µm, Sample 40: 161 µm, Sample 41: 141 µm), the microbend loss is larger than 1 dB / km. Also, when the outer diameter of the secondary coating is larger than 200 µm (Sample 39: 201 µm, Sample 40: 181 µm, Sample 41: 201 µm), the microbend loss is larger than 1 dB / km. Comparing Samples 39 to 41, the microbend loss can be reduced when the "coating thickness ratio" is larger than 0.3. [Explanation of symbols]
[0044] 10...core, 20...clad, 100...optical fiber, 100a...glass fiber (glass portion), 210...primary coating, 220...secondary coating.
Claims
1. a glass portion extending in a direction of a central axis; the glass portion is made of silica-based glass, includes a core including the central axis and doped with chlorine at a mass fraction of 1% or more, and a cladding surrounding the core and having a refractive index lower than the maximum refractive index of the core, and has substantially consistent residual stress throughout a cross section of the glass portion perpendicular to the central axis; a first average value of residual stress in a region in the cross section of the glass portion that is spaced from a center of the cross section along a radial direction by a distance of 50 μm or more and 62.5 μm or less is lower than a second average value of residual stress in a region in the cross section that is spaced from a center of the cross section along a radial direction by a distance of 45 μm or more and 55 μm or less; The larger the difference value obtained by subtracting the first average value from the second average value, the smaller the transmission loss. Optical fiber.
2. The difference between the maximum and minimum values of the residual stress is 200 MPa or less.
2. The optical fiber of claim 1.
3. The difference between the maximum and minimum values of the residual stress is 100 MPa or less; The optical fiber of claim 2.
4. The core further comprises fluorine. The optical fiber according to any one of claims 1 to 3.
5. The mass fraction of the fluorine in the core is 0.1% or more; 5. The optical fiber of claim 4.
6. the mass fraction of fluorine in the core is less than or equal to 0.5%; 5. The optical fiber of claim 4.
7. The mass fraction of chlorine in the core is 1.5% or more; The optical fiber according to any one of claims 1 to 6.
8. The mass fraction of chlorine in the core is 3% or less; The optical fiber according to any one of claims 1 to 7.
9. 70μm 2 150 μm or more 2 having an effective cross-sectional area of The optical fiber according to any one of claims 1 to 8.
10. The α value that defines the shape of the refractive index profile in the core is 150 or less. The optical fiber according to any one of claims 1 to 9.
11. The α value is 3 or more and 99 or less. The optical fiber of claim 10.
12. In the cross section of the glass portion, a value obtained by subtracting an average value of residual stress in a region that is 55 μm or more and 62.5 μm or less away from the center of the cross section along the radial direction from an average value of residual stress in a region that is 45 μm or more and 55 μm or less away from the center of the cross section along the radial direction is greater than 20 MPa. The optical fiber according to any one of claims 1 to 11.
13. Has a microbend loss of 1 dB / km or less at a wavelength of 1550 nm. The optical fiber according to any one of claims 1 to 12.
14. After being exposed to a hydrogen atmosphere having a partial pressure of 1.5 kPa and a temperature of 25° C. for 720 hours, the optical fiber experiences an increase in transmission loss of 0.005 dB / km or less at a wavelength of 1550 nm. The optical fiber according to any one of claims 1 to 13.
Citation Information
Patent Citations
Low loss optical fiber and method of making the same
JP2016081067A
Low-loss optical fiber with core region co-doped with fluorine and chlorine
JP2018516386A
Method and apparatus for reducing stress between depositions within a substrate tube
US20030056549A1
High chlorine content low attenuation optical fiber
WO2016007806A1